2014
DOI: 10.1007/s13365-014-0254-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impairment associated with predominantly early stage HIV infection in Abuja, Nigeria

Abstract: Detailed neuropsychological testing was performed on 134 HIV seropositive (SP) and 77 HIV seronegative (SN) individuals, 86% with early stage HIV infection in Nigeria, to determine the frequency of HIV-related neurocognitive impairment among the HIV-infected group. Twenty-two tests were administered to assess the following seven ability domains: speed of information processing (SIP); attention/working memory (AWM); executive functioning (EF); learning (LN); memory (MEM); verbal fluency (VF); and motor speed/de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 23 publications
3
38
0
3
Order By: Relevance
“…Clinical data characterizing the samples were scarcely reported. While three studies revealed no difference in gait speed between PLHIV naïve or mixed (treated/untreated) and uninfected adults in Uganda , two studies from Nigeria showed a lower gait speed among PLHIV naïve or treated in comparison with those uninfected . No information is available on balance.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data characterizing the samples were scarcely reported. While three studies revealed no difference in gait speed between PLHIV naïve or mixed (treated/untreated) and uninfected adults in Uganda , two studies from Nigeria showed a lower gait speed among PLHIV naïve or treated in comparison with those uninfected . No information is available on balance.…”
Section: Resultsmentioning
confidence: 99%
“…Details of these are described in our other reports (Akolo et al 2014; Royal et al 2016; Jumare et al 2017). Participants were screened for effort using the Hiscock Digit Memory Test, and for depression with the Beck Depression Inventory (Beck et al 1996).…”
Section: Methodsmentioning
confidence: 94%
“…Details of these are described in our other reports (Akolo et al 2014; Royal et al 2016). In brief, the following ability domains and individual tests within the domains were examined: speed of information processing (WAIS-III Digit Symbol, WAIS-III Symbol Search, Color Trails Test 1 and Trail Making Test A); attention/working memory (Paced Auditory Serial Addition Task, and WMS-III Spatial Span); executive function (Color Trails Test 2 and Stroop Color and Word Test), learning (Hopkins Verbal Learning Test – Revised [HVLT-R] total learning and the Brief Visuospatial Memory Test – Revised [BVMT-R] total learning); memory (HVLT-R delayed recall; BVMT-R delayed recall); verbal fluency (Letter (Word Sound Fluency; Category Fluency: Nouns (animals) and Category Fluency: Verbs [actions]); motor speed and dexterity (Grooved Pegboard Test, Finger Tapping Test and Timed Gait).…”
Section: Methodsmentioning
confidence: 93%